Development of Adsorbent Materials Using Residue from Coffee Industry and Application in Food dye Adsorption Processes - Luiz Eduardo Nochi de Castro; Débora Alessandra Jones Battocchio; Leomara Floriano Ribeiro; Leda Maria Saragiotto Colpini (Brazilian Archives of Biology and Technology, 2022)
Abstract The aim of this study was to develop an adsorbent from coffee husk, residue from the coffee industry by different activation methods and to evaluate its application in the treatment of effluent containing synthetic Ponceau 4R dye. The activations were with phosphoric acid and zinc chloride, then the samples were characterized in terms of physical and chemical composition, structure and morphology, thermal behavior and kinetic and thermodynamic study. Regarding the characterization of the material, the activation with phosphoric acid showed porous morphology and a high surface area (429.7 m2 g-1) and with the kinetic study it was possible to obtain an equilibrium time of 60 min and dispersion according to Elovich kinetics (R2 = 0.96 and RMSE < 0.24). According to the experimental design, the adsorptive capacity can be evaluated with the significant result (qe = 19.87 mg g-1) under the conditions of 90 min of the adsorption process and at the concentration of 2 g L-1 of adsorbent. In relation to the equilibrium study the Langmuir model fit the data with coefficient of determination of R2 = 0.84. Finally, the Ponceau 4R dye adsorption process using coffee husks as an activated carbon was thermodynamically favorable through the negative Gibbs free energy and positive entropy (+0.022 kJ mol-1 K-1). Therefore, the use of coffee husk as activated carbon proved to be a favorable material for Ponceau 4R dye adsorption.